Efficacy of immunotherapy in small cell lung cancer: A retrospective stude - Marina A. Lyadova; Denis S. Fedorinov; Julia S. Mansurova; Evgeniya S. Kuzmina; Yury S. Esakov; Konstantin V. Lyadov; Vsevolod N. Galkin; Irina V. Poddubnaya (ZAO "Consilium Medicum", 2024)
Background. Small cell lung cancer (SCLC), predominantly due to smoking, is a highly differentiated, rapidly growing epithelial cell carcinoma of high malignancy originating from bronchial neuroendocrine cells. Almost 70% of SCLC patients have metastases at the time of diagnosis, which requires the use of drug therapies, including immunotherapy. Aim. To evaluate the efficacy and safety of immune checkpoint inhibitors in patients with small cell lung cancer. Materials and methods. One hundred and twenty one patients (90 men and 31 women) aged 44 to 84 years were included in the retrospective multicentre non-randomised study. The majority (90.9%) of patients were treated in the 1st line of therapy. IT were administered in the 2nd line and subsequent lines of treatment in 9.1% of patients. Weakened (ECOG 2-3) state at the time of treatment initiation was noted in 30 (24.8%) patients. Results. Progression-free survival in patients with SCLC receiving 1st-line treatment was 5.82 (95% CI 3.92-7.72) months, and 2nd-line and beyond was 6.21 (95% CI 0.76-11.66) months. Survival in patients with small-cell lung cancer receiving 1st-line IT was 8.0 (95% CI 6.18-9.81) months, and 2nd-line or longer was 11.3 months (95% CI 4.31-18.29) months (p=0.108). Objective response was achieved in 43 (35.5%) patients, of whom 38 (34.5%) were on first-line IT and 5 (45.5%) patients were on 2nd or more. iAEs grade 3-4 was observed in only 18 (14.9%) patients. Conclusion. Immunotherapy for SCLC allows achieving high rates of objective response and disease control. This method of treatment is characterized by insignificant number of grade 3-4 immune-mediated adverse events, which indicates an acceptable safety profile.